Evaluation of stationary phases based on silica hydride for the analysis of drugs of abuse. Issue 17 (4th September 2013) - Pesek, Joseph J.; Matyska, Maria T.; Kim, Amy M.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> Several stationary phases based on silica hydride were evaluated as possible separation media for drugs of abuse. In the RP mode both a C18 and a phenyl column were tested using ACN/water and methanol/water mobile phases with formic acid or ammonium formate as modifiers. Detection was performed using MS, so separation of isobaric species was a factor in selecting the column, mobile phase composition, and gradient. A number of sample preparation procedures were also included as part of determining the most appropriate experimental protocol on these types of stationary phases. Morphine was used as a model for developing a protocol that would be suitable for the analysis of hydrophilic drugs.